The business of being an editor: Norman Lockyer, Macmillan and Company, and the editorship of Nature, 1869–1919. (19th April 2020) - Baldwin, Melinda
Abstract: Broadly speaking, Victorian scientific periodicals fell into one of two categories: specialist periodicals aimed at publishing original research for an audience of scientific researchers, or popularizing periodicals meant to share news about science with a broader readership. When astronomer Norman Lockyer founded Nature in 1869, he envisioned his new weekly as a member of the latter group. That vision resulted partly from his own wish to raise science's profile in Great Britain and partly from the interests of his publisher Macmillan and Company, which bankrolled Nature with its eye on eventual profit. This paper shows that the pressure for Nature to be a financial success shaped Lockyer's approach to editing and thus shaped Nature 's content, leading the magazine to occupy an unusual space in the landscape of Victorian science publishing and placing unique burdens on its editor. Nature quickly moved away from Lockyer's initial vision of a popularizing magazine and became known as a periodical by and for researchers. The magazine's popularity among scientific researchers set it apart from its closest inspiration, the commercial weekly Chemical News . But in contrast to contemporary editors at learned society journals, such as George Gabriel Stokes at the Philosophical Transactions, Lockyer did not linger over the scientific details of Nature 's papers. Instead, articles for Nature were usually either accepted or rejected immediately, with little editorial involvement shaping their scientific content. The difference between editing Nature and editing other research periodicals is clearly visible in the selection of Richard Gregory as Lockyer's successor in 1919. Most research periodicals selected eminent men of science as their editors‐in‐chief. Gregory, a science writer and long‐time subeditor at Nature, did not lend scientific prestige to the masthead, but was eminently qualified to maintain Nature 's distinctive content and its profitability for Macmillan and Company.